Simulation, and application of water content determination process of single well crude oil. (2018) - Xiong, Zhaohong
The water content data of wellhead crude oil is an important basis for determining the production accounting of oil fields, the adjustment of block unit and the effectiveness of the single well operation, which is related to enterprise cost effectiveness. For a long time, distillation method has been used in water cut analysis of wellhead crude oil in Shengli Oilfield of China, resulting in serious oil and gas volatilisation, great safety hazard and excessive consumption of solvent oil and so on. To solve these problems, this paper explored the assay method for the moisture content of crude oil, carried out feasibility analysis of distillation method, capacitance method, electrically extrication method and centrifuge method. Based on the simulations, the distillation method and centrifuge method were optimised and compared by field experiments, and the method for testing water content of crude oil in single well was improved. The improved method has been applied in the oil production plant, which has achieved a good effect of reducing cost and increasing efficiency compared with the original method.